Forming a Caring Generation: Integration of Environmental Ethics in Fish Cultivation Learning for Early Childhood - Shahzadi Hina; Solikhatin Solikhatin (Journal of Psychological Insight, 2025)
Environmental degradation highlights the need to cultivate environmental awareness and ethical values from an early age through education. This study aims to examine how integrating environmental ethics into fish cultivation learning influences environmental awareness and prosocial behavior in early childhood education. Using a qualitative descriptive approach, the research involved early childhood learners, teachers, and parents in an early childhood education setting, with data collected through observations, interviews, and documentation of learning activities. The findings reveal that integrating ethical principles, such as responsibility, care for living beings, and environmental respect, into practice-based fish cultivation activities led to observable behavioral changes. Children demonstrated increased responsibility in caring for fish, cooperative behavior during group tasks, and the transfer of pro-environmental attitudes to daily life at home. The novelty of this study lies in positioning fish cultivation not merely as a technical activity but as an ethical learning medium for character formation. The study recommends incorporating ethics-oriented, experiential environmental learning into early childhood curricula to foster sustainable and caring behavior from an early age.